Relationships between operational practices and performance among early adopters of green supply chain management practices in Chinese manufacturing enterprises - Zhu, Qinghua; Sarkis, Joseph (Journal of Operations Management, 2004)
AbstractGlobalization results in both pressure and drivers for Chinese enterprises to improve their environmental performance. As a developing country, China has to balance economic and environmental performance. Green supply chain management (GSCM) is emerging to be an important approach for Chinese enterprises to improve performance, possibly on both these dimensions. Using empirical results from 186 respondents on GSCM practice in Chinese manufacturing enterprises, we examine the relationships between GSCM practice and environmental and economic performance. Using moderated hierarchical regression analysis, we evaluate the general relationships between specific GSCM practices and performance. We then investigate how two primary types of management operations philosophies, quality management and just‐in‐time (or lean) manufacturing principles, influence the relationship between GSCM practices and performance. Significant findings were determined for a number of relationships. Managerial implications are also identified.